Chemie im Kontext: The Students´ View on its Adaption in Spain and Argentina – Two Case Studies - Sánchez Díaz, Ignacio; Pérgola, Martín; Galagovsky, Lydia; Di Fuccia, David-Samuel; Valente, Beatriz (Scientia in educatione, 2018)
One of the main problems in science education nowadays, and especially in chemical education, is that the students usually cannot perceive the relevance of what they learn in their classes. There have been some efforts to improve the student interest and motivation without diminishing the understanding of the chemistry concepts. The context-based methodologies allow the students to see the relevance and applicability of what they learn in the chemistry classes, connecting the canonical science with their lives, interests and previous knowledge. One of these methodologies, Chemie im Kontext (Chemistry in Context in German), was developed in Germany to improve chemistry teaching in secondary education. Its main features include the use of contexts throughout the whole teaching unit and the effort to foster student self-learning. At present, there is an ongoing project, supported by the German Academic Exchange Service (DAAD), to assess the use of a German context-based methodology, Chemie im Kontext (ChiK in the following) in four secondary schools in the Madrid region (Spain). Based on a collaboration with the University of Buenos Aires (Argentina) this case study has been accompanied by a second one carried out in Buenos Aires during 2015 and 2016. The main goal of this project is to identify which changes students and teachers perceive when comparing a ChiK teaching unit to the traditional teaching approach. This article focuses on the students’ opinions concerning the use of a ChiK methodology in chemistry classes in Spain and Argentina and therefore allows a first insight into possible effects of this teaching approach.